2017
DOI: 10.1002/app.44832
|View full text |Cite
|
Sign up to set email alerts
|

Annealing effect on crystalline structure and mechanical properties in long glass fiber reinforced polyamide 66

Abstract: Generally, annealing is one of the important post-processing methods used to obtain injection molding products coupled with excellent comprehensive performance. Based on a series of experimental studies in this work, a systematic investigation was performed to research the annealing effect on crystalline structure and mechanical properties in long glass fiber reinforced polyamide 66 (LGF-PA66) composite. The composite was prepared by injection molding, using LGF-PA66 pellet with 50 wt % fiber content and 12 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 32 publications
0
11
0
1
Order By: Relevance
“…They can be easily reprocessed, post thermoformed, joined and repaired by welding or solvent bonding [48][49][50]. Because of all these features, thermoplastic composites are widely employed in many fields, such as the transportation industry, where they are used to realize structural/semi structural parts like bumpers, front end modules and dashboard frames [51,52]. Among all the FRTs, those having a polyamide (PA) based matrix and a long (continuous or discontinuous) fiber reinforcement are the most widely used today, thanks to their high mechanical properties and relatively low cost [52].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They can be easily reprocessed, post thermoformed, joined and repaired by welding or solvent bonding [48][49][50]. Because of all these features, thermoplastic composites are widely employed in many fields, such as the transportation industry, where they are used to realize structural/semi structural parts like bumpers, front end modules and dashboard frames [51,52]. Among all the FRTs, those having a polyamide (PA) based matrix and a long (continuous or discontinuous) fiber reinforcement are the most widely used today, thanks to their high mechanical properties and relatively low cost [52].…”
Section: Introductionmentioning
confidence: 99%
“…Because of all these features, thermoplastic composites are widely employed in many fields, such as the transportation industry, where they are used to realize structural/semi structural parts like bumpers, front end modules and dashboard frames [51,52]. Among all the FRTs, those having a polyamide (PA) based matrix and a long (continuous or discontinuous) fiber reinforcement are the most widely used today, thanks to their high mechanical properties and relatively low cost [52]. To the best of our knowledge, no papers dealing with the development of structural thermoplastic composites with TES capability can be found in the open scientific literature, since the small number of research works on multifunctional structural composites with TES properties focus on composites with a thermosetting matrix.…”
Section: Introductionmentioning
confidence: 99%
“…From Fig. a and b, it has been obviously found that the section of unaged specimens is equipped with the largest number of fracture state of GFs and lesser fiber pull‐out . At the same time, the surface of GFs is covered with a great deal of matrix resins and the fracture surfaces of fiber pull‐out are accompanied with fewer remaining holes, indicating that good interface interaction exists in the unaged samples between PA10T and GF.…”
Section: Resultsmentioning
confidence: 87%
“…As shown in Figure 4, the peak fitting is performed when the draw ratio is 2.00 times. The 2θ angles of the two new reflection spots are respectively 20.82 • and 21.62 • , corresponding to (100) and (110)/(010) of the α-crystal of PA1010 [45][46][47]. It shows that the α-crystal structure is formed in the course of simultaneous thermal stretched γ-PA1010, and the α-crystal and γ-crystal structure of the PA1010 exist simultaneously.…”
Section: Structural Evolution Of -Pa1010mentioning
confidence: 99%